2002
DOI: 10.1046/j.1365-2133.2002.04784.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and histochemical changes pertaining to active and healed cutaneous tuberculosis

Abstract: Effective antituberculous chemotherapy will lead to a substantial reduction of fibrosis and the consequent disability that can arise in patients with tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Fibronectin is an extracellular matrix protein with adhesion function that constitutes the scaffold for the deposition of collagens and proteoglycans in fibrosis (Jayasankar et al 2002 ; Marshall et al 1996 ). In this study, consistent expression of fibronectin was observed in the extracellular space, forming a network in the center of stages I, II and III tuberculous granulomas in lung and mediastinal lymph node.…”
Section: Discussionmentioning
confidence: 99%
“…Fibronectin is an extracellular matrix protein with adhesion function that constitutes the scaffold for the deposition of collagens and proteoglycans in fibrosis (Jayasankar et al 2002 ; Marshall et al 1996 ). In this study, consistent expression of fibronectin was observed in the extracellular space, forming a network in the center of stages I, II and III tuberculous granulomas in lung and mediastinal lymph node.…”
Section: Discussionmentioning
confidence: 99%